The Effect of Digital Health Education Using Video on Handwashing Behavior After Flooding Among Children - Lestari, Wahyuni Tri; Sriyono; Laili, Rokhmatus; Dewi, Lingga Curnia; Khunkumhaeng, Naraporn (Gaceta Médica de Caracas, 2026)
Introduction: Handwashing is essential for preventing disease transmission after a flood disaster. Video-based health education can be an effective method to improve knowledge, attitudes, and handwashing practices among children. This study aims to investigate the impact of video-based digital health education on improving handwashing behavior among children following flooding.